Digitalization, education and skills development in the global South: An assessment of the debate with a focus on Sub-Saharan Africa - Margarita Langthaler; Homa Bazafkan (Austrian Foundation for Development Research (ÖFSE), 2020)
The COVID-19 pandemic has intensified discussions about the digital revolution. Digitalization of ever-more sectors of society appears to be the only possible answer to the requirements of physical distancing. The education sector stands out as one example. Yet, the pandemic has also brought to light the pitfalls of accelerated digitalization in terms of rising inequality and exclusion. In development policy, digitalization has been commonly referred to as a major opportunity for economic development. Much lower used to be the attention paid to risks such as the digital divide. Human capabilities rank as one of the key preconditions to reap the benefits of digitalization. Digitalization of education and training systems appears to be the order of the day. Yet, there is lack of consistent strategies to do so without deepening existing patterns of inequality and exclusion, in particular in the Global South. This Briefing Paper will initially analyse the lessons of experience from the COVID-19 pandemic and its impact on the education and TVET (Technical and vocational education and training) sector. It will then reflect on the framing of the debates on digitalization in education. The academic discussion will be summarised from two perspectives, first with regard to the skills required for a digitalized economy and second analysing the impact of digitalization on education systems, mainly in Sub-Saharan Africa. The Paper will subsequently comment on current trends in digitalization policies for the education sector as well as in development cooperation. Conclusions will outline a few recommendations at the policy level.
Keywords: 330; digitalization; education; TVET; Global South; digital skills; inequalities; development cooperation